Visualization of synaptic inhibition with an optogenetic sensor developed by cell-free protein engineering automation - Grimley, Joshua S. (2014)
We describe an engineered fluorescent optogenetic sensor, SuperClomeleon, that robustly detects inhibitory synaptic activity in single, cultured mouse neurons by reporting intracellular chloride changes produced by exogenous GABA or inhibitory synaptic activity. Using a cell-free protein engineering automation methodology that bypasses gene cloning, we iteratively constructed, produced, and assayed hundreds of mutations in binding-site residues to identify improvements in Clomeleon, a first-generation, suboptimal sensor. Structural analysis revealed that these improvements involve halide contacts and distant side chain rearrangements. The development of optogenetic sensors that respond to neural activity enables cellular tracking of neural activity using optical, rather than electrophysiological, signals. Construction of such sensors using in vitro protein engineering establishes a powerful approach for developing new probes for brain imaging.